2021
DOI: 10.3390/rs13040626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differences in Structure from Motion Software on Image Processing of Unmanned Aerial Vehicle Photography and Estimation of Crown Area and Tree Height in Forests

Abstract: This study examines the effects of differences in structure from motion (SfM) software on image processing of aerial images by unmanned aerial vehicles (UAV) and the resulting estimations of tree height and tree crown area. There were 20 flight conditions for the UAV aerial images, which were a combination of five conditions for flight altitude, two conditions for overlap, and two conditions for side overlap. Images were then processed using three SfM programs (Terra Mapper, PhotoScan, and Pix4Dmapper). The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
(133 reference statements)
0
13
0
Order By: Relevance
“…Agisoft Metashape and Pix4Dmapper were found to have better performance than Con-textCapture, which had a worse accuracy of point cloud models reconstruction than other software due to limitations in the performance of the image matching algorithm [51,52]. In addition, Pix4Dmapper was found to have similar performance [51,[53][54][55] with Agisoft Metashape in accuracy of point cloud models reconstruction and have better density [51] than Agisoft Metashape.…”
Section: Point Cloud Reconstructionmentioning
confidence: 93%
“…Agisoft Metashape and Pix4Dmapper were found to have better performance than Con-textCapture, which had a worse accuracy of point cloud models reconstruction than other software due to limitations in the performance of the image matching algorithm [51,52]. In addition, Pix4Dmapper was found to have similar performance [51,[53][54][55] with Agisoft Metashape in accuracy of point cloud models reconstruction and have better density [51] than Agisoft Metashape.…”
Section: Point Cloud Reconstructionmentioning
confidence: 93%
“…Individual DBH and stand-level estimates of basal area, stand density, and canopy cover (CC) are commonly used as forest mensuration metrics. Kameyama and Sugiura [ 58 ] estimated the CA and TH using different SfM software such as Terra Mapper (version 2.5.1), PhotoScan (version 1.3.2.4205), and Pix4Dmapper (version 4.5.6) on aerial image processing by UAV at different altitudes. The UAV has been used successfully in several recent studies to predict the DBH distribution of trees [ 59 ], mean TH [ 60 ], and aboveground CST [ 10 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Inter-sensor comparisons reveal differences in surface reconstruction and reflectance values between common consumer-grade UAS platforms (Sona et al, 2014;Yanagi and Chikatsu, 2016). Moreover, other studies have found differences in mapping products produced by different SfM software packages for forested (Fraser and Congalton, 2018;Kameyama and Sugiura, 2021) and unvegetated (Sona et al, 2014;Yanagi and Chikatsu, 2016) areas. Variability introduced by UAS flight protocols and UAS-SfM workflows for mapping dynamic coastal wetland environments has not yet been well explored.…”
Section: Introductionmentioning
confidence: 95%